Ticagrelor alone vs. ticagrelor plus aspirin following percutaneous coronary intervention in patients with non-ST-segment elevation acute coronary syndromes: TWILIGHT-ACS. (20th October 2020) - Baber, Usman; Dangas, George; Angiolillo, Dominick Joseph; Cohen, David Joel; Sharma, Samin Kumar; Nicolas, Johny; Briguori, Carlo; Cha, Jin Yu; Collier, Timothy; Dudek, Dariusz; Džavik, Vladimir; Escaned, Javier; et al.
Abstract: Aims : The aim of this study was to determine the effect of ticagrelor monotherapy on clinically relevant bleeding and major ischaemic events in relation to clinical presentation with and without non-ST elevation acute coronary syndromes (NSTE-ACS) among patients undergoing percutaneous coronary intervention (PCI) with drug-eluting stents (DES). Methods and results : We conducted a pre-specified subgroup analysis of The Ticagrelor With Aspirin or Alone in High Risk Patients After Coronary Intervention (TWILIGHT) trial, which enrolled 9006 patients with high-risk features undergoing PCI with DES. After 3 months of dual antiplatelet therapy (DAPT) with ticagrelor plus aspirin, 7119 adherent and event-free patients were randomized in a double-blind manner to ticagrelor plus placebo versus ticagrelor plus aspirin for 12 months. The primary outcome was Bleeding Academic Research Consortium (BARC) type 2, 3, or 5 bleeding while the composite of all-cause death, myocardial infarction (MI), or stroke was the key secondary outcome. Among patients with NSTE-ACS ( n = 4614), ticagrelor monotherapy reduced BARC 2, 3, or 5 bleeding by 53% [3.6% vs. 7.6%; hazard ratio (HR) 0.47; 95% confidence interval (CI) 0.36–0.61; P < 0.001) and in stable patients ( n = 2503) by 24% (4.8% vs. 6.2%; HR 0.76; 95% CI 0.54–1.06; P = 0.11; nominal P int = 0.03). Rates of all-cause death, MI, or stroke among those with (4.3% vs. 4.4%; HR 0.97; 95% CI 0.74–1.28; P = 0.84) and without (3.1% vs. 3.2%; HR 0.96; 95% CI 0.61–1.49; P = 0.85) NSTE-ACS were similar between treatment arms irrespective of clinical presentation ( P int = 0.96). Conclusion : Among patients with or without NSTE-ACS who have completed an initial 3-month course of DAPT following PCI with DES, ticagrelor monotherapy reduced clinically meaningful bleeding events without increasing ischaemic risk as compared with ticagrelor plus aspirin. The benefits of ticagrelor monotherapy with respect to bleeding events were more pronounced in patients with NSTE-ACS. Trial registration: Clinicaltrials.gov identifier: NCT02270242. Graphical Abstract: